2017
DOI: 10.1371/journal.pone.0187809
|View full text |Cite
|
Sign up to set email alerts
|

An electronic health record based model predicts statin adherence, LDL cholesterol, and cardiovascular disease in the United States Military Health System

Abstract: HMG-CoA reductase inhibitors (or “statins”) are important and commonly used medications to lower cholesterol and prevent cardiovascular disease. Nearly half of patients stop taking statin medications one year after they are prescribed leading to higher cholesterol, increased cardiovascular risk, and costs due to excess hospitalizations. Identifying which patients are at highest risk for not adhering to long-term statin therapy is an important step towards individualizing interventions to improve adherence. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our study demonstrates the power of utilizing EHR to capture a high-risk cohort of patients with severe hypercholesterolemia, whose treatment can be optimized with affordable and low-risk medications in order to prevent future adverse outcomes. The potential implications for providing a pragmatic approach to identify both patient-specific and system-wide care gaps are tremendous [ [34] , [35] , [36] , [37] , [38] , [39] ]. With an enhanced ability to pinpoint these patients, we will also have opportunities to develop and capitalize on novel implementation strategies to actually improve patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates the power of utilizing EHR to capture a high-risk cohort of patients with severe hypercholesterolemia, whose treatment can be optimized with affordable and low-risk medications in order to prevent future adverse outcomes. The potential implications for providing a pragmatic approach to identify both patient-specific and system-wide care gaps are tremendous [ [34] , [35] , [36] , [37] , [38] , [39] ]. With an enhanced ability to pinpoint these patients, we will also have opportunities to develop and capitalize on novel implementation strategies to actually improve patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with international evidence, 98,103,104 we found obesity to be a positive factor in medication persistence, which may relate to patients' perception of their obesity putting them at increased risk of a subsequent CVD event, thus, motivating their greater general interest in their health including medication adherence. Previous studies have shown that the initial refill history has the potential to improve subsequent medication adherence prediction for new therapy users 40,48 and past refill history was suggested as a significant factor for medication adherence prediction in primary prevention. 105 Our BRT, SVM, and ANN models using both forward and backward variable selection processes, demonstrated that variables related to past adherence behavior (e.g., past refill history, days between the latest prehospitalization dispensing date, and the hospital admission date) improved the prediction performance.…”
Section: Methods Of Information In Medicinementioning
confidence: 99%
“…Among the few relevant studies, random forest (RF) and boosted regression tree (BRT) have been applied to predict medication adherence among patients who were new to statin or statin combination drugs achieving cross-validated c-statistics of 0.81 and 0.842, respectively. 40,48 Although not a cross-validated estimation of prediction accuracy, Bourdès et al observed that a one hidden layer neural network performed better than LR for predicting medication persistence for patients with acute coronary syndrome after the first hospital discharge. 49 Prediction of high risk for readmission has been used successfully as the basis for CDSS in hospital discharge planning.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital EHR, on the contrary, provide a more complete picture of the patient [26] as they can be considered as a quasi-electronic form of the patient record [27]. Those diagnosis codes are presumably more accurate and are complemented by additional data sources such as laboratory values [28]. However, this information is not standardized and therefore complicates subsequent analysis steps.…”
Section: Plos Onementioning
confidence: 99%